2011
DOI: 10.5858/2009-0652-oar2
|View full text |Cite
|
Sign up to set email alerts
|

The Oncofetal Protein IMP3: A Novel Molecular Marker to Predict Aggressive Meningioma

Abstract: N Context.-One of the major clinical challenges is to predict recurrence of meningioma. Recently, we have found that IMP3, an oncofetal RNA-binding protein, is a biomarker to predict aggressive tumors.Objective.-To investigate whether IMP3 can be used as a new biomarker to predict the recurrence and overall survival of patients with meningiomas.Design.-One hundred seven patients with primary meningiomas were investigated for expression of IMP3 by immunohistochemistry and whether expression of this molecule cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Like p53 expression, tumors with high Ki-67 PI more frequently showed IMP3 expression. This observation has been documented in other tumors like hepatocellular carcinoma, B cell lymphoma, meningioma, and bile duct carcinoma 14,27,28,29. With these findings, IMP3 is considered to be a better prognostic marker than p53 or Ki-67 and these three proteins may be closely connected.…”
Section: Discussionmentioning
confidence: 66%
“…Like p53 expression, tumors with high Ki-67 PI more frequently showed IMP3 expression. This observation has been documented in other tumors like hepatocellular carcinoma, B cell lymphoma, meningioma, and bile duct carcinoma 14,27,28,29. With these findings, IMP3 is considered to be a better prognostic marker than p53 or Ki-67 and these three proteins may be closely connected.…”
Section: Discussionmentioning
confidence: 66%
“…It has been shown that positive IMP3 immunohistochemical expression is of significant prognostic value in renal cell carcinoma, pancreatic ductal carcinoma, hepatocellular carcinoma, colonic adenocarcinoma, gastric adenocarcinoma, endometrioid adenocarcinoma, Merkel cell carcinoma, non-small cell lung cancer, meningioma, urothelial carcinoma, and mammary carcinoma, with an increased risk of developing metastases in patients with IMP3-positive tumors versus IMP3-negative tumors and an increased frequency of IMP3 expression in high-grade tumors versus low-grade tumors [6,12,14,19,27,28,32,35,42,[57][58][59][60][61][62][63]66]. In addition, IMP3 was found to be expressed more often in triple-negative (estrogen receptor, progesterone receptor, HER2) invasive mammary carcinomas than in non-triple-negative tumors [67].…”
Section: Introductionmentioning
confidence: 99%
“…Other genetic non-NF2 aberrations of oncogenes have been observed in skull base and higher-grade meningiomas [12,[24][25][26]. The Glu17Lys mutation of the AKT1 (chromosome 14q32.32) gene was one of the mutations found in tumor cell lines that had no genetic alterations in the NF2 gene.…”
Section: Molecular Genetics Of Grade Ii/iii Meningioma (Atypical/anapmentioning
confidence: 99%
“…This causes an over active Akt kinase (protein kinase B) which excessively phosphorylates factors of the AKT/PKB pathway when it should be in the "off" position. This leads to an increase in the level of YAP that potentially can suppress the expression of pro-apoptotic genes that activate after cellular DNA damage [12,[23][24][25][26]. The GADD45A was once thought to be a potential genetic target for meningioma and other tumor pathogenesis; however, no genetic abnormalities were found in meningioma cell lines.…”
Section: Molecular Genetics Of Grade Ii/iii Meningioma (Atypical/anapmentioning
confidence: 99%
See 1 more Smart Citation